Implementation of School-Based Management for Improving the Quality of Education at Linggang Bigung Public Senior High School - Afriyanti, Afriyanti; Gede Mulawarman, Widyatmike; Dwiyono, Yudo; Komariyah, Laili; Haryaka, Usfandi; Akhmad, Akhmad (Borneo Educational Journal (Borju), 2025)
School-Based Management (SBM) is an educational management approach that grants schools autonomy to manage resources and make independent decisions by involving principals, teachers, parents, and the community to improve education quality. This study aims to describe the implementation of SBM at Linggang Bigung Public Senior High School as a strategic effort to enhance school quality. Using a qualitative approach with a case study method, the research focuses on the planning, implementation, evaluation, and supervision processes of SBM at SMAN 1 and SMAN 2 Linggang Bigung. Data were collected through interviews with principals, teachers, students, and parents, as well as through documentation analysis related to SBM implementation. The findings indicate that the implementation of SBM successfully created a learning environment more relevant to the needs of students and the community, while also increasing transparency and accountability in school management. Evaluations conducted at both schools showed significant achievements in academic performance and student character development. However, follow-up actions on evaluation results still require optimization, particularly in strengthening corrective measures and improving facilities and infrastructure. Furthermore, the principals’ leadership, characterized by adaptive and transformational styles, effectively motivated teachers and staff to innovate in teaching practices. In conclusion, active participation from all stakeholders—including teachers, students, parents, and school committees plays a crucial role in reinforcing SBM implementation, which in turn contributes to comprehensive improvements in education quality.